Peran Employee Relations Dalam Upaya Pencapaian Visi dan Misi Best Western Premier Solo Baru - Yusia Putriani Handoko (PAX HUMANA, 2017)
Employee relations is an activity that serves to build communication relations within the internal public of an organization in an effort to achieve the goals of the organization. Employees are an important asset for companies to manage besides the material assets. As one of hospitality industry, Best Western Premier Solo Baru also conducts employee relations activities to achieve its vision and mission. Since it was inaugurated on December 15, 2015, Best Western Premier Solo New held employee relations activities for its employees as a mean to develop relationships among employees related to the vision and mission of Best Western that has to be achieved. This research uses qualitative research methods. Data retrieval is done by interviewing informants and do direct observation. Through this research will answer questions about what employees' relations which are conducted by Best Western Premier Solo Baru, the meaning behind the vision and mission of Best Western, and the relation between employee relations activities as an effort to achieve vision and mission of Best Western. From this research, will be obtained the data that to achive vision and mission, employee relations is done by embedding the values of Best Western's organization culture, I-CARE and performing 12 work commitments at Best Western. Key words: Best Western Premier, Solo Baru, Employee Relations, Vision and Mission